Formalising Priority Ceiling Protocol with Dynamic Adjustment of Serialization Order in Real Time Databases - Ban, Doan Van; Ngu, Nguyen Huu; Huong, Ho Van (VNU Journal of Science: Mathematics - Physics; Vol 19 No 1, 2003)
Abstract